1973
DOI: 10.1037/h0034707
|View full text |Cite
|
Sign up to set email alerts
|

Interview decisions as determined by competency and attitude similarity.

Abstract: 1962) reported on the comparison of the replies of candidates with the judge's replies on a selfdescription form and found inconsistent results for predicting and acceptance or rejection of the candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 12 publications
4
40
0
1
Order By: Relevance
“…Competency, experience, or qualifications seem to be far more important than anything else (such as age) in predicting interview or selection decisions (e.g., Baron 1993;Baskett 1973;Locke-Connor and Walsh 1980;Rasmussen 1984;Singer and Bruhns 1991;Weiner and Schneiderman 1974). This point is often neglected in laboratory studies that artificially hold these important variables constant.…”
Section: General Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Competency, experience, or qualifications seem to be far more important than anything else (such as age) in predicting interview or selection decisions (e.g., Baron 1993;Baskett 1973;Locke-Connor and Walsh 1980;Rasmussen 1984;Singer and Bruhns 1991;Weiner and Schneiderman 1974). This point is often neglected in laboratory studies that artificially hold these important variables constant.…”
Section: General Summary and Discussionmentioning
confidence: 99%
“…The first of these studies was by Baskett (1973), who examined the effect of attitude similarity and competency on hiring recommendations and salary offers. Fifty-one undergraduate students were asked to evaluate a hypothetical job candidate for the position of vice president.…”
Section: Laboratory Research Examining Age Discrimination In the Emplmentioning
confidence: 99%
“…Early research in the similarity-attraction paradigm hypothesized that individuals would be evaluated less favorably and would achieve less social standing in the group to the extent that they are demographically different from other group members (Byrne, Clore, and Worchel, 1966; Baskett, 1973;Kanter, 1977). Group members are thought to favor similar others because similarity on a social attribute provides mutual reinforcement or "consensual validation" of attitudes and beliefs that underlie the attribute, while reinforcing the value of the attribute itself (Byrne, Clore, and Worchel, 1966: 223).…”
Section: Demography and Influencementioning
confidence: 99%
“…For example, Baskett (1973) found that similar applicants were rated as being more competent, but were not more likely to be recommended for a job.…”
Section: Age and Race Of The Intervieweementioning
confidence: 99%